Active training : - Silberman, Mel (John Wiley & Sons, 2006)
The third edition of Active Training, provides a thorough introduction to the core principles of active training design and delivery and includes a wealth of examples, tips, and techniques. The book has been revised to reflect the latest trends in workforce training and key sections, such as assessment and evaluation, have been thoroughly updated. In addition, a completely new chapter has been included to cover the design of active training for e-learning and online applications.